Smart Modulators Based on Electric Field-Triggering of Surface Plasmon-Polariton for Active Plasmonics - Švanda, Jan; Kalachyova, Yevgeniya; Mareš, David; Siegel, Jakub; Slepička, Petr; Kolská, Zdeňka; Macháč, Petr; Michna, Štefan; Švorčík, Václav; Lyutakov, Oleksiy (Nanomaterials (Basel, Switzerland), 2022)
Design and properties of a plasmonic modulator in situ tunable by electric field are presented. Our design comprises the creation of periodic surface pattern on the surface of an elastic polymer supported by a piezo-substrate by excimer laser irradiation and subsequent selective coverage by silver by tilted angle vacuum evaporation. The structure creation was confirmed by AFM and FIB-SEM techniques. An external electric field is used for fine control of the polymer pattern amplitude, which tends to decrease with increasing voltage. As a result, surface plasmon-polariton excitation is quenched, leading to the less pronounced structure of plasmon response. This quenching was checked using UV-Vis spectroscopy and SERS measurements, and confirmed by numerical simulation. All methods prove the proposed functionality of the structures enabling the creation smart plasmonic materials for a very broad range of advanced optical applications.
Keywords: plasmon excitation; thin layers; SERS; modification; sensor; nanostructures; smart materials; LIPSS; polymer